1992
DOI: 10.1159/000186707
|View full text |Cite
|
Sign up to set email alerts
|

Study on Chronic Renal Injuries Induced by Carbon Tetrachloride: Selective Inhibition of the Nephrotoxicity by Irradiation

Abstract: Carbon tetrachloride (CC14) was intraperitoneally injected into Balb/c mice 4 times at biweekly intervals, and the morphological changes of the liver and kidney were examined during 12 weeks after the last injection. The renal injuries progressed in spite of cessation of CC14 treatment; microcysts with tubular-cell degeneration were manifest on day 42 after the last injection of CC14. At the end of the experiment, however, interstitial fíbrosis with inflammatory cell infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
(7 reference statements)
4
19
0
Order By: Relevance
“…Once filtered, low-molecular-weight proteins are reabsorbed and metabolized by the proximal tubule cells. High level of proteinurea and haematuria in urine of this study showed the nephrotoxicity induced with KBrO 3 (Ogawa et al, 1992).The present study revealed that oral administration of L. procumbens significantly improved creatinine and urobilinogen, and decreased the elevated levels of proteinuria and haematuria. Present study revealed that administration of KBrO 3 caused marked impairment in renal function along with significant oxidative stress in the kidneys.…”
Section: Discussionsupporting
confidence: 64%
“…Once filtered, low-molecular-weight proteins are reabsorbed and metabolized by the proximal tubule cells. High level of proteinurea and haematuria in urine of this study showed the nephrotoxicity induced with KBrO 3 (Ogawa et al, 1992).The present study revealed that oral administration of L. procumbens significantly improved creatinine and urobilinogen, and decreased the elevated levels of proteinuria and haematuria. Present study revealed that administration of KBrO 3 caused marked impairment in renal function along with significant oxidative stress in the kidneys.…”
Section: Discussionsupporting
confidence: 64%
“…However, the pathogenesis of CCl 4 -induced renal injury has not been clearly clarified. While Rincon et al (1999) showed that effects of CCl 4 on kidney structure and function depended on the functional state of the liver, Ogawa et al (1992) suggested etiologic independence of the renal Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,9,10,28 However, the pathogenesis of CCl 4 -induced renal dysfunction has not been elucidated. While Rincon and co-workers 29 showed that the effects of CCl 4 on kidney structure and function depended on the functional state of the liver, Ogawa and co-workers 30 suggested aetiologic independence of the renal and hepatic events. It has been reported that systemically-administered CCl 4 in rats became distributed at higher concentrations in the kidney than in the liver.…”
Section: Discussionmentioning
confidence: 99%